THE INFLUENCE OF BLUE LIGHT FROM NATURAL AND ARTIFICIAL SOURCES ON THE SKIN - Filipovic, Mila; Pecarski, Danijela; Marinovic, Dubravka; Rodic, Branka; Lukic, Milica (HEALTH CARE, 2023)
Blue light includes rays of lower energy in comparison to UV radiation, but it has a greater power of penetrating the dermis, even to a depth of 1mm. The aim of this review article was to analyze the biological effects of natural and artificial blue light on the skin based on the available literature, as well as to propose preventive measures in order to protect the skin from its harmful effects. The latest research has shown that blue light has various direct and indirect effects on the skin. The direct effects of blue light on the skin are the excessive creation of reactive oxygen species, nitrogen, and hyperpigmentation, and it indirectly affects the skin by disrupting the circadian rhythm and secreting melatonin. Blue light has a direct effect on chromophores that are present in the skin and leads to their activation. Their activation leads to the excessive production of reactive oxygen species and release of reactive nitrogen species, that is, nitrogen monoxide (NO), which triggers melanogenesis and hyperpigmentation. Also, there comes to a decrease in cell vitality and/or proliferation of keratinocytes and melanocytes, then increased synthesis of pro-inflammatory interleukins and tumor necrosis factor-alpha and altered collagen metabolism. Blue light reduces the antioxidative protection of the skin by causing the degradation of present carotenoids. It can be used in clinical practice in the prevention and treatment of certain dermatoses, as well as in photorejuvenation treatments in aesthetic medicine. Further research in this field is necessary.
Keywords: blue light, skin, prevention